Towards health equity: core components of an extended home visiting intervention in disadvantaged areas of Sweden - Madelene Barboza; Anneli Marttila; Bo Burström; Asli Kulane (BMC, 2022)
Abstract Background Understanding the mechanisms of implementation of public health interventions in community settings is a key aspect of programme assessments. To determine core components and establish a programme theory are important tools to improve functioning and support dissemination of programme models to new locations. An extended early childhood home visiting intervention has been developed on-site in a socioeconomically disadvantaged area of Sweden since 2013 with the aim of reducing persisting health inequities in the population. This study aimed at investigating the core programme components and how the intervention was perceived to contribute towards health equity from early childhood. Methods Qualitative framework method was applied in a document analysis and subsequent semi-structured interviews with 15 key actors involved in the programme. Results The intervention was found to be constituted of five core components centred around the situation-based, parental strengthening work method delivered by a qualified team of child health care nurse and social worker. The programme theory foresaw positive effects on child and parental health, responsive parenting practices, families' use of welfare services according to need and increased integration and participation in society. The principles of Proportionate Universalism were recognised in the programme theory and the intervention was perceived as an important contribution to creating conditions for improved health equity for the families. Still, barriers to health equity were identified on the structural level which limit the potential impact of the programme. Conclusions The core components of the Extended home visiting programme in Rinkeby correspond well to those of similar evidence-based home visiting interventions. Combining focus on early childhood development and responsive parenting with promoting access to the universal welfare services and integration into society are considered important steppingstones towards health equity. However, a favourable macro-political environment is required in the endeavour to balance the structural determinants' influence on health inequities. Improved availability and accessibility to welfare services that respond to the needs of the families regarding housing, education and employment are priorities. Trial registration The study was retrospectively registered on 11/08/2016 in the ISRCTN registry ( ISRCTN11832097 ).